2013
DOI: 10.1007/s00267-013-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change on Coffee Farms in Southern Guatemala and its Environmental Consequences

Abstract: Changes in commodity prices, such as the fall in coffee prices from 2000 to 2004, affect land use decisions on farms, and the environmental services they provide. A survey of 50 farms showed a 35% loss in the area under coffee between 2000 and 2004 below 700 m with the majority of this area (64 %) being coffee agroforest systems that included native forest species. Loss of coffee only occurred on large and medium-scale farms; there was no change in area on cooperatives. Coffee productivity declined below 1,100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 22 publications
3
32
0
1
Order By: Relevance
“…Therefore, conversions of land between these three agroforests can significantly alter the bird communities found in the landscape. Currently, there is some evidence that areca growers in the region are switching to rubber, and we expect that, at a landscape scale, this will have significant impacts on bird communities (Robbins et al, 2015), as has occurred in Guatemala (Haggar et al, 2013) and Costa Rica (Karp et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, conversions of land between these three agroforests can significantly alter the bird communities found in the landscape. Currently, there is some evidence that areca growers in the region are switching to rubber, and we expect that, at a landscape scale, this will have significant impacts on bird communities (Robbins et al, 2015), as has occurred in Guatemala (Haggar et al, 2013) and Costa Rica (Karp et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results have direct consequences for current land-sharing management practices including land conversions (change in crop type), pesticide use, maintaining understory and native tree cover. Given the sensitivity of coffee, rubber and areca cropping strategies, particularly with shifting farm gate prices, current subsidy packages, costs of inputs and labor, as well as larger cultural and political conditions (Hausermann, 2014;Robbins et al, 2015;Warren-Thomas et al, 2015), the conservation of biodiversity in the Ghats requires linking of land-sharing and land-sparing approaches (Das et al, 2006;Karp et al, 2012;Haggar et al, 2013). Policy shifts and role of global-local markets for these commodities will need to further "value" these landscapes to ensure effective biodiversity conservation outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…While Soto Pinto et al (2000) observed that tree density did not affect coffee yields in Chiapas, Mexico; Haggar et al (2013) found that the diverse shade species coffee systems in neighbouring Guatemala had lower productivity than shaded coffee with just one shade species.…”
Section: Costs and Benefits To Farmers Maintaining High Diversity Shamentioning
confidence: 96%
“…Impacts of intensification included water pollution from agrochemical run-off, reduced forest cover and habitat loss, soil erosion and consolidation of plantations under large landowners (DaMatta 2004;Polzot 2004). When coffee prices fall, shaded coffee systems have been replaced with other land uses that offer fewer environmental benefits such as rubber plantations or pasture (Haggar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During the previous decade, prices were lower and very variable, which caused the abandonment of many coffee plantations. Haggar et al (2013) reported that coffee growers of Guatemala were negatively affected by the constant changes in prices, especially from 2000 to 2004, forcing coffee growers into other agricultural crops such as sugarcane. This led to environmental problems because of the greater generation of greenhouse gases due to changes in the use of machinery, crops, fertilization needs, etc.…”
Section: Coffee Profitabilitymentioning
confidence: 99%